Sustainable Strategies for Solving Perennial Water Crisis in Enugu Using Infiltration/Sump Technology - Egbo , Philips Nnajiofor; Anih , Stephen Chibuike; Obinna , Collins Nnamani (American Journal of Environment Studies, 2022)
Purpose: Perennial water crises is a monster that threatens the very essence of human existence globally. Efforts have been made to stamp out water crises by the provision of pipe borne water, artisanal well, etc but to no avail. Notwithstanding these efforts, a visit to the streets of Enugu showed the excruciating hardship faced by the people as a result of scarcity of portable water. This study aimed at determining the current condition of portable water supply, challenges to sustainable water supply as well as suitability and sustainability of harvesting portable water through infiltration/sump technology adaptation in solving Enugu metropolis water crises. Methodology: The survey and experimental research methods were used. A total number of 48 water samples were aseptically collected from 3 points on a weekly basis. The points are A: from the flowing Asata River, B: from the infiltration sump and, C: from the locally fabricated water treatment plant. These samples were subjected to physical, chemical and biological analysis to determine the level of impurities, chemical and biological pollutants contained therein. Atomic Absorption Spectrophotometer (AAS) was used to determine the concentration of heavy metals in the water samples. Direct culture plate count was used to determine bacterial load while sample concentration method was used for the microscopic examination. Findings: The results were presented in tables and analyzed with simple percentages. It was discovered that water supply to Enugu residents has been abysmally low compared to the Enugu State Water Corporation (ENSWC) installed capacity. Out of the six (6) years under study, the highest annual water production of 6,082,962 m3 representing 12.62% of the installed capacity, supplied to the inhabitants of Enugu metropolis was achieved in the year 2018. The study discovered that the raw Asata River is contaminated with (a) heavy metals, (b) E. coli and Coliforms (c) debris, non-metallic contaminants etc. However, with the application of sump/infiltration technology and minimal treatment the river is a veritable and sustainable alternative to the epileptic pipe borne water supply from ENSWC to the inhabitants. Recommendation: Adaptation and application of sump/infiltration smart indigenous water harvesting technology in solving the perennial water crisis in Enugu metropolis is recommended.